'The whole nation on one station'? National FM as a case study of radio for indigenous small linguistic communities in Zimbabwe - Ndawana, Tariro (Centre for Film and Media Studies, 2019)
This thesis is an institutional ethnography of National FM as the only PSB radio that broadcasts in all local languages. It examines the feasibility of having one radio station broadcasting in all the indigenous languages of Zimbabwe. Language rights are pivotal in human development and many countries have developed many ways that can be used to promote them. The media have also been used in preservation of language rights (AMARC, 2014). However, many minorities are deprived of their language rights. Previous research in Zimbabwe on small indigenous communities, have looked at general rights and the right to education. Available literature on radio has also studied content and concentrated on Radio Zimbabwe. This thesis explores both the promotion of language rights and the involvement of radio in the preservation of minority languages. It delves into the forces behind the production of local minority languages at National FM. The institutional ethnography encompassed the use of observation, in-depth interviews with sixteen participants and document analysis. It also used content analysis of all programmes that are Barwe, Chikunda, Doma and Hwesa which have the smallest number of speakers in the country (Hachipola, 1998; Magwa, 2008; Ndlovu, 2009). This study proves that National FM is not fully representing all the minority languages. The political economy of the station and sociology of journalism directly affect the production. National FM, like all PSB radio stations in the country has gone commercial. Management is now focusing on generating revenue than promoting language rights. National FM broadcasts in Shona and Ndebele instead of the minority languages. ZBC management consists of Shona and Ndebele speakers and decision making is done by people who are not minority language speakers. Content analysis of the four selected languages indicates that the languages which have been dominated are still marginalized as National FM broadcasts current affairs programmes only for the selected languages. These languages are given very little broadcast time and the programmes are not interactive.